The growth and valuation of generic skills - Andy Dickerson; Francis Green (University of Kent, Department of Economics, 2002)
Using a method for measuring job skills derived from survey data on detailed work activities, we show that between 1997 and 2001 there was a growth in Britain in the utilisation of computing skills, literacy, numeracy, technical know-how, high-level communication skills, planning skills, client communication skills, horizontal communication skills, problem-solving and checking skills. Computer skills and high-level communication skills carry positive wage premia, as shown both in cross-section hedonic wage equations and through a within-sohorts change analysis. No part of the gender pay gap can be accounted for by differences in levels of generic skills between men and women.
Keywords: J31; 330; skills; wages; computers; Betriebliches Bildungsmanagement; Qualifikation; Lohn; Großbritannien